2015
DOI: 10.1530/joe-14-0701
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic hyperplasia after gastric bypass surgery in a GK rat model of non-obese type 2 diabetes

Abstract: Gastric bypass surgery produces clear antidiabetic effects in a substantial proportion of morbidly obese patients. In view of the recent trend away from 'bariatric' surgery and toward 'metabolic' surgery, it is important to elucidate the enhancing effect of bypass surgery on pancreatic b-cell mass, which is related to diabetes remission in non-obese patients. We investigated the effects of gastric bypass surgery on glycemic control and other pancreatic changes in a spontaneous non-obese type 2 diabetes Goto-Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
2
9
1
Order By: Relevance
“…Rather than increase observed previously, a decrease in pancreatic β-cell mass was shown due to the reduction in pancreatic steatosis and decreased pancreatic insulin content, a phenomenon suggested to be linked to pancreas adaptation following weight loss. Similarly to heterogeneous findings in humans, animal model studies report either enhanced 101,102 or decreased 95,103,104…”
Section: Changes In Hormones and Beta Cell Functionmentioning
confidence: 72%
“…Rather than increase observed previously, a decrease in pancreatic β-cell mass was shown due to the reduction in pancreatic steatosis and decreased pancreatic insulin content, a phenomenon suggested to be linked to pancreas adaptation following weight loss. Similarly to heterogeneous findings in humans, animal model studies report either enhanced 101,102 or decreased 95,103,104…”
Section: Changes In Hormones and Beta Cell Functionmentioning
confidence: 72%
“…13 On the other hand, in diabetic GK rats, multiple and bigger effects on islet architecture have been reported, including pancreatic hyperplasia, enlarged beta cell-mass, and increased ratio of beta cells to non-beta endocrine cells. 14 Similar surgery-mediated changes were also described in diet-induced obese (DIO) mice in association with increased islet numbers, 15 implying a direct influence of bariatric surgery on pancreatic cellular turnover and islet structure. Although several factors are likely to cause this, it is now clear that alteration in enterohormone release is one of the major effector.…”
Section: Improvement In Islet Function Is Crucial For Diabetes Remissmentioning
confidence: 75%
“…Few studies have reported beta-cell morphology, and in all of these, including the present study, only larger beta-cell mass and/or stronger insulin staining were detected in RYGB, SG, DJB or IT animals compared with their diabetic control. It is regrettable that no comparison was performed between pre- and postoperative rats[35-37]. Therefore, there has been no evidence supporting islets hyperplasia or beta-cell turnover after bariatric surgeries until now.…”
Section: Discussionmentioning
confidence: 99%